Knowledge and the body-mind problem : in defence of interaction - Popper, Karl R; Notturno, M. A (Routledge, 2000)
\'Here, Popper\'s ideas are expressed with a beguiling simplicity and with considerable humour and charm. The enthusiasm (and, occasionally, puzzlement) of the original audience is preserved in the records of discussions following each lecture. The volume serves as an excellent introduction to Popper\'s later thought for those who think philosophy beyond them.\' o| Roger Caldwell, Literary Review Based on lectures given in 1969 by Sir Karl Popper at Emory University, Popper argues forcefully that the problem of the interaction between mental and physical states is still open regardless of assertions by materialist philosophers\' that it has \'evaporated\'.
Keywords: znalost výsledků (psychologie); Memory; paměť; psychologie, klinická psychologie; Knowledge of Results, Psychological